Description of Parents Knowledge About Nutritional Status of Ages 1 - 3 Years in Sidomulyo Puskesmas area Samarinda city. - Rita Puspa Sari (Jurnal Kesehatan Pasak Bumi Kalimantan, 2020)
Background: Parental education is very important because it can influence the development of children's nutrition because by knowing nutrition, parents can find out the weight gain/nutrition of children under five every month. Knowledge about nutrition becomes a very important part of maintaining children's growth and development. Nutritional status in toddlers must be very guarded and taken seriously from parents because malnutrition occurs at this time can cause irreversible damage. It is very possible that short body size is one indicator or indication of prolonged malnutrition in infants. More fatal malnutrition will have an impact on brain development. The nutritional status of children under five can be influenced by several factors, including the lack of insight and knowledge of mothers about nutrition, the low level of maternal education also contributes greatly to the cases of malnutrition that are often found in the community. Objective: This study aims to determine the level of parental knowledge about the nutritional status of children aged 1-3 years in the area of Sidomulyo Samarinda Puskesmas. Method: This type of research conducted in this research is descriptive design with a quantitative approach. The sample used in this study were 40 children. The tool used in collecting data is the questionnaire method. Results: This study illustrates the level of parental knowledge about the nutritional status of children, with respondents mothers who have children aged 1-3 years in which mothers with a good level of knowledge as many as 28 people (70%), who have enough knowledge of 8 people (20%), and less than 4 people (10%).Keywords: Knowledge, Nutritional status, children aged 1-3 years